(untitled) (Journal of Scientific Research, 2022)
Microbial corrosion behavior of mild steel was studied by exposing mild steel coupons in Barr’s medium inoculated with sulfate-reducing bacteria (Desulfovibrio desulphuricans). During the investigation, a considerable loss in weight and deterioration of microstructure of mild steel coupons surface was observed. Coupons were further exposed to culture media containing different concentrations of metronidazole (MNZ) and 2- methylimidazole (MIZ) inhibitors. The corrosion behavior of mild steel was measured by weight loss, electrochemical studies, and SEM. Polarization studies indicated the mixed-type behavior of these inhibitors. MNZ and MIZ exhibited 82.23 and 78.30 % inhibition efficiencies, respectively, as revealed by polarization measurements. The results show that the inhibition efficiencies increased with inhibitor concentration. The surface analysis was performed by scanning electron microscopy (SEM).